Desert Environments Facilitate Unique Evolution of Biosynthetic Potential in Streptomyces - Kunjukrishnan Kamalakshi Sivakala; Karina Gutiérrez-García; Polpass Arul Jose; Thangadurai Thinesh; Rangasamy Anandham; Francisco Barona-Gómez; Natesan Sivakumar (Molecules, 2021)
Searching for new bioactive metabolites from the bacterial genus Streptomyces is a challenging task. Combined genomic tools and metabolomic screening of Streptomyces spp. native to extreme environments could be a promising strategy to discover novel compounds. While Streptomyces of desertic origin have been proposed as a source of new metabolites, their genome mining, phylogenetic analysis, and metabolite profiles to date are scarcely documented. Here, we hypothesized that Streptomyces species of desert environments have evolved with unique biosynthetic potential. To test this, along with an extensive characterization of biosynthetic potential of a desert isolate Streptomyces sp. SAJ15, we profiled phylogenetic relationships among the closest and previously reported Streptomyces of desert origin. Results revealed that Streptomyces strains of desert origin are closer to each other and relatively distinct from Streptomyces of other environments. The draft genome of strain SAJ15 was 8.2 Mb in size, which had 6972 predicted genes including 3097 genes encoding hypothetical proteins. Successive genome mining and phylogenetic analysis revealed the presence of putative novel biosynthetic gene clusters (BGCs) with low incidence in another Streptomyces. In addition, high-resolution metabolite profiling indicated the production of arylpolyene, terpenoid, and macrolide compounds in an optimized medium by strain SAJ15. The relative abundance of different BGCs in arid Streptomyces differed from the non-arid counterparts. Collectively, the results suggested a distinct evolution of desert Streptomyces with a unique biosynthetic potential.